Induction and morpho-chemical characterization of Stevia rebaudiana colchiploids - YADAV, ASHOK KUMAR; SINGH, S; YADAV, SUBHASH C; DHYANI, D; BHARDWAJ, GARIMA; SHARMA, ANJALI; SINGH, BIKRAM (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted to produce higher biomass-yielding stevia Stevia rebaudiana (Bertoni) with larger leaf size and high glycoside content. To improve leaf yield and sweet glycoside content found in the leaves of the plant, polyploidy was induced by treating the seeds with colchicine. Treatment of seeds with 0.2% colchicine and above (up to 0.6%) reduced the survival rate of stevia young seedlings to below 50%. Maximum number of polyploids (tetraploids) were obtained with 0.6% colchicine treatment for 24 hr; mixoploidy was observed at 0.2% colchicine treatment for 6 hr. It however needs further experimentation for more precise information. The nuclear DNA content (2C-value of diploid Stevia rebaudiana variety Madhuguna) was estimated by flow-cytometry (FCM) to be 2.72pg. Polyploids C7-3-4, C7-35, C9-1-1 and C9-4-3 could be distinguished from diploid control plants as they had double the DNA content, suggesting autotetraploidy. Chromosome count in root-tip cells of polyploids (2n=44) confirmed their tetraploid status as compared with the control (2n=22). The autotetraploids in stevia had significantly increased leaf size, thickness and chlorophyll content and reduced internode length. Tetraploid stevia genotypes are important germplasm for further improvement of stevia biomass and glycoside content.